Race to injustice: lessons learned from the Duke Lacrosse rape case - Seigel, Michael L. (Carolina Academic Press, 2009)
The facts and only the facts / Robert L. Luck and Michael L. Seigel -- Faculty reactions, contentious debate, and academic freedom / Robert M. O'Neil -- The town-gown relationship / Sharon Rush -- Alcohol consumption on college campuses / George W. Dowdall -- Invisible criminality : male peer-support groups, alcohol, and the risk of aggressive sexual behavior / Michelle S. Jacobs -- Black Venus Hottentot revisited : gratuitous use of women of color's bodies and the role of race and gender in campus and academic reactions / Michele Alexandre -- Racial politics and discretion in criminal law / Janine Young Kim -- The Duke lacrosse players and the media : why the fair trial-free press paradigm doesn't cut it anymore / Andrew E. Taslitz -- When prosecutorial discretion meets disaster capitalism / Lenese Herbert -- The Duke defendants reaped the benefits of a zealous defense-but do only the rich get real lawyers? / Rodney Uphoff -- An examination of the district attorney's alleged unethical conduct / Kenneth Williams -- The moment of truth : the decision to institute charges in a rape case / Michael L. Seigel -- The Duke lacrosse rape investigation : how not to do eyewitness- -- Identification procedures / Gary L. Wells, Brian L. Cutler, and Lisa E. Hasel -- DNA profiling / Paul C. Giannelli -- Presuming guilt or protecting victims? : analyzing the special treatment of those accused of rape / Aviva Orenstein